2021
DOI: 10.1038/s41598-021-89383-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in health-related quality of life measured by the Sarcoidosis Health Questionnaire

Abstract: Sarcoidosis is granulomatous disease, which complex etiology is yet to be fully discovered. In the majority of cases its course is self-limiting. However it can have different clinical manifestations and can be debilitating condition with great impact on health-related quality of life (HRQL). The aim of our study was to assess if there are any differences in HRQL dependent to gender. We examined a group of 33 males and 42 females (with no differences in mean age, disease activity, TLCO, FEV1, FVC, FEV1/FVC) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…As Fernández-de-las-Peñas and colleagues note, our results also suggest that female sex might be related to a worse HRQOL perception in terms of symptoms after the acute infection, even if the disease is less severe during that phase. This has been also observed in other conditions like chronic fatigue [ 7 ], connective tissue disorders [ 8 ], diabetes mellitus [ 9 ], or cardiovascular diseases like atrial fibrillation [ 10 ]. This effect seems to be independent of the severity of these illnesses [ 1 , 6 , 8 , 10 , 11 ].…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…As Fernández-de-las-Peñas and colleagues note, our results also suggest that female sex might be related to a worse HRQOL perception in terms of symptoms after the acute infection, even if the disease is less severe during that phase. This has been also observed in other conditions like chronic fatigue [ 7 ], connective tissue disorders [ 8 ], diabetes mellitus [ 9 ], or cardiovascular diseases like atrial fibrillation [ 10 ]. This effect seems to be independent of the severity of these illnesses [ 1 , 6 , 8 , 10 , 11 ].…”
mentioning
confidence: 79%
“…This has been also observed in other conditions like chronic fatigue [ 7 ], connective tissue disorders [ 8 ], diabetes mellitus [ 9 ], or cardiovascular diseases like atrial fibrillation [ 10 ]. This effect seems to be independent of the severity of these illnesses [ 1 , 6 , 8 , 10 , 11 ]. Additionally, a worse overall perception of health has been noted among women in healthy general population samples [ 12 , 13 , 14 ], independent of age and educational or income status [ 11 , 14 , 15 ].…”
mentioning
confidence: 79%
“…Men and women exhibit different biological, behavioral, social, and cultural characteristics. Sex-related differences are apparent in social interactions, lifestyles, health perceptions, and actions individuals take to influence their health status [37,38]. A recent systematic review and meta-analysis found that women had more symptoms of depression and anxiety than men [19,20].…”
Section: Discussionmentioning
confidence: 99%